THE CHALLENGES OF VENDORS’ SELECTION: ASSESSING THE STRATEGIC STEPS OF MITIGATING THE CHALLENGES - Olawale AMUZAT; Ndifreke Akaninyene ENO (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The study analyzed the challenges to vendor selection: assessing the strategic steps of mitigating the challenges. Vendor Selection is one of the crucial decisions frequently executed by many industries. In recent times, the number of suppliers has increased enormously depending on a wide range of criteria. For many organizations, effective vendor selection is of vital importance. As the pace of market globalization quickens, the number of potential vendors and factors to consider when selecting vendors’ increases. While selecting vendors, organizations encounter a multitude of challenges that can impact the efficiency, effectiveness, and overall success of their operations. These challenges stem from various factors, including vendor reliability, compatibility, cost considerations, and risk management. Overcoming vendor selection challenges requires a systematic approach that involves careful planning, evaluation, and decision-making. Start by clearly defining your organization's needs, objectives, and priorities. Research the market to identify potential vendors that offer products or services aligned with your requirements. On this basis, the study concluded that in many projects there are bound to be critical success factors and they have much impact on vendor selection. The critical success factors include the work sequence with a timeline that an individual can demonstrate in his/her plan to meet the project timeline. As it is the work sequence with timeline includes strict adherence to the project scope, provision of the project timeline, evaluation of the procurement document, milestone, selection of the right procurement strategy, preparation of work sequence document, and many more. One of the recommendations made was that the project manager must be proactive and do due diligence early on with the project to lead as required including developing a progress review to track if indeed the project is meeting its intended delivery plan.